VARIANTS OF THE COURSE OF GLOMERULONEPHRITIS AND THEIR ETIOPATHOGENESIS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Glomerulonephritis is an immune-inflammatory kidney disease with predominant damage to the glomeruli, but also involving the tubules and interstitial tissue. Glomerulonephritis, by its development mechanism, belongs to the group of infectious-allergic diseases. The term "infectious-allergic" reflects the formation of infectious allergy in combination with various non-immune damage to the organ.